Citrus Greening (Huanglongbing; HLB) Blight and Tristeza Comparison Identification Sheet - Megan M. Dewdney; Jamie D. Yates; Ronald H. Brlansky; Timothy M. Spann; Michael E. Rogers (EDIS)
PP263, a 2-page English/Spanish ID sheet by M.M. Dewdney, J.D. Burrow, R.H. Brlansky, T.M. Spann, and M.E. Rogers, guides identification of Citrus Greening and provides a comparison chart for Citrus Greening, Blight, and Tristeza. Published by the UF Department of Plant Pathology, April 2009.